Determination of halonitromethanes and haloacetamides: An evaluation of sample preservation and analyte stability in drinking water - Liew, Deborah; Linge, Kathryn; Joll, Cynthia; Heitz, Anna; Charrois, Jeffrey (Elsevier BV, 2012)
Simultaneous quantitation of 6 halonitromethanes (HNMs) and 5 haloacetamides (HAAms) was achieved with a simplified liquid–liquid extraction (LLE) method, followed by gas chromatography–mass spectrometry. Stability tests showed that brominated tri-HNMs immediately degraded in the presence of ascorbic acid, sodium sulphite and sodium borohydride, and also reduced in samples treated with ammonium chloride, or with no preservation. Both ammonium chloride and ascorbic acid were suitable for the preservation of HAAms. Ammonium chloride was most suitable for preserving both HNMs and HAAms, although it is recommended that samples be analysed as soon as possible after collection. While groundwater samples exhibited a greater analytical bias compared to other waters, the good recoveries (>90%) of most analytes in tap water suggest that the method is very appropriate for determining these analytes in treated drinking waters. Application of the method to water from three drinking water treatment plants in Western Australia indicating N-DBP formation did occur, with increased detections after chlorination. The method is recommended for low-cost, rapid screening of both HNMs and HAAms in drinking water.